Metabolic perturbations in classic galactosemia beyond the Leloir pathway: Insights from an untargeted metabolomic study. Issue 2 (22nd January 2019) - Taylor Fischer, S.; Frederick, Allison B.; Tran, ViLinh; Li, Shuzhao; Jones, Dean P.; Fridovich‐Keil, Judith L.
Abstract: Classic galactosemia (CG) is an autosomal recessive disorder that impacts close to 1/50000 live births in the United States, with varying prevalence in other countries. Following exposure to milk, which contains high levels of galactose, affected infants may experience rapid onset and progression of potentially lethal symptoms. With the benefit of early diagnosis, generally by newborn screening, and immediate and lifelong dietary restriction of galactose, the acute sequelae of disease can be prevented or resolved. However, long‐term complications are common, and despite many decades of research, the bases of these complications remain unexplained. As a step toward defining the underlying pathophysiology of long‐term outcomes in CG, we applied an untargeted metabolomic approach with mass spectrometry and dual liquid chromatography, comparing thousands of small molecules in plasma samples from 183 patients and 31 controls. All patients were on galactose‐restricted diets. Using both univariate and multivariate statistical methods, we identified 252 differentially abundant features from anion exchange chromatography and 167 differentially abundant features from C18 chromatography. Mapping these discriminatory features to putative metabolites and biochemical pathways revealed 14 significantly perturbed pathways; these included multiple redox, amino acid, and mitochondrial pathways, among others. Finally, we tested whether any discriminatory features also distinguished cases with mild vs more severe long‐term outcomes and found multiple candidates, of which one achieved false discovery rate‐adjusted q < 0.1. These results extend substantially from prior targeted studies of metabolic perturbation in CG and offer a new approach to identifying candidate modifiers and targets for intervention.